Defending the Body Without Sensing the Body Position: Physiological Evidence in a Brain-Damaged Patient With a Proprioceptive Deficit - Fossataro, Carlotta; Bruno, Valentina; Gindri, Patrizia; Garbarini, Francesca (Frontiers in Psychology, 2018)
The ability to know where our body parts are located in space (proprioception) is fundamental for both successfully interacting with the external world and monitoring potential threats. In this case-control study, we investigated whether the absence of proprioceptive signals may affect physiological defensive responses. To this aim, a right brain-damaged patient with a left upper-limb proprioceptive deficit (P+ patient) and age-matched healthy controls, underwent the recording of the Hand-Blink Reflex (HBR). This defensive response, elicited by electrical stimulation of the median nerve and recorded from the orbicularis oculi, is modulated by the hand position: it is enhanced when the threatened hand is near to the face, inside the defensive peripersonal-space (DPPS). According to the classical neuropsychological perspective, we used P+ patient as a model to investigate the role of proprioception in HBR modulation, by manipulating the congruity/incongruity between the intended and actual positions of the stimulated hand. P+ patient, with his eyes closed, had to voluntarily place his left hand either far from or near to his face and to relieve the arm’s weight over a supporting device. Then, in congruent conditions, the hand was stimulated in the actual (intended) position. In incongruent conditions, the patient’s hand was moved by the examiner from the intended to the opposite (not-intended) position and then stimulated. We observed an inverse response pattern between congruent and incongruent conditions. In congruent conditions, P+ patient showed an HBR enhancement in near compared to far position, comparable to that found in healthy controls. This suggests that, even in absence of proprioceptive and visual information, the HBR modulation was still present. Conversely, in incongruent conditions, P+ patient showed a greater HBR magnitude for far position (when the hand was actually far, but the patient intended it to be near) than for near position (when the hand was actually near, but the patient intended it to be far). This result suggests that proprioceptive signals are not necessary for HBR modulation to occur. It relies more on the intended than on the actual position of the hand. The role of motor intention and planning in shaping the DPPS is discussed.